Impacted Canines Classification Systems Among Orthodontic Patients: Life Sciences-Orthodontics - Alfarra , Yahya H. Y.; Noorani, Tahir Yusuf; Asif, Jawaad Ahmed; Wan Ahmad, Wan Muhamad Amir; Ahmad Rajion, Zainul (International Journal of Life Science and Pharma Research, 2022)
This review covers all aspects from the viewpoint of impacted canines that were missed by some articles. Most review studies focus on the epidemiology and incidence of the disease but rarely on the detailed investigation of this therapeutic disorder; therefore, appropriate awareness of canine impaction diagnosis and management is critical prior to any orthosurgical treatment procedures. Hence, it is crucial to emphasize the means of proper diagnosis and interception of this clinical condition. This study aimed to compare and review the various diagnostic methods used to identify canine impaction, its advantages, shortcomings, research, and clinical implications to guide the evaluation and management of cases in general dental practice. Based on the current literature, the epidemiology of canine impaction, diagnosis, classification systems, and surgical options for exposing impacted canines are discussed. To determine the anatomical position of impacted canines, a thorough clinical examination and appropriate diagnostic imaging should be performed. The surgical method for exposing impacted canines should consider the tooth’s anatomical position in regard to the alveolar ridge and the amount of keratinized mucosa/gingiva. The article concludes that displacement and non-eruption of impacted canines can be managed by administering an accurate and adequate diagnosis of canine impaction, proper investigation of tooth position, length, direction, and related structures, selecting the appropriate management approach, and also reducing the biomechanics involved during canine retraction using fixed orthodontic appliances when they are impacted, and thus can restrict the risk of s urgical t rauma o n t he a djacent h ard a nd s oft t issues in th e p atients . T his a rticle m ay su ggest th at 3 D im aging is re quired to as sist cl inicians in de veloping a su ccessful t reatment p lan f or d etecting i mpaction a nd t he s urrounding structures . CPD/Clinical Relevance: Canine impactions are frequent during routine examinations. Appropriate identification, investigation, and, if necessary, referral are crucial to the outcome o f t reatment s uccess.